Spectrophotometric Determination of Vanadium, Chromium and Manganese Reagents and Methods - Goswami, Ajay Kumar (De Gruyter Reference, 2024)
The present book is part of series published on Spectrophotometric methods for determination of various transition metals. Since vanadium chromium and manganese are most important industrial metals their analysis using simple and inexpensive methods is of utmost importance. The present book is an important milestone in this area. Most of the methods described are simple yet well evidenced developed by the experts of the area. The book is written in do it yourself style in lucid and comprehensive way so that analyst with no prior expertise can use it. Academia, industry and Pharma sector analyst will be true beneficiaries of this book